223k views
1 vote
Complete the steps to solve this linear equation: 2x + 9(x – 1) = 8(2x + 2) – 5

1.Apply the distributive property:                 2x + 9x– 9 = 16x + 16 – 5

2.Combine like terms on each side:                11x – 9 = 16x + 11

3.Use the subtraction property of equality to isolate the variable term: –9 = 5x + 11

 Use the subtraction property of equality to isolate the constant:   –20 = 5x

4. Use the division property of equality to solve: = x

2 Answers

7 votes

Answer:

-4

Explanation:

User DoruAdryan
by
5.2k points
4 votes

Answer:

-4 is the correct answer hope i helped

Explanation:

User Leonid Beschastny
by
6.0k points